High Salt Intake Is Independently Associated With Hypertensive Target Organ Damage. Issue 4 (22nd September 2015) - Imaizumi, Yuki; Eguchi, Kazuo; Murakami, Takeshi; Arakawa, Kimika; Tsuchihashi, Takuya; Kario, Kazuomi
Abstract : The authors tested the hypothesis that high salt intake is associated with hypertensive target organ damage (TOD) independent of blood pressure (BP), and oxidative stress is a modifying factor of this association. A total of 369 community‐dwelling Japanese adults (mean age, 67.5 years; 56.6% women) were examined in this observational study. At the patients' annual health check‐ups, urinary salt excretion (U‐SALT), 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG), and albumin‐creatinine ratio (UACR) were measured from first morning urine. U‐SALT (β=0.14, P =.016) and 8‐OHdG (β=0.13, P =.018) were both independently associated with logUACR. U‐SALT was associated with TOD independent of BP level, and oxidative stress may be a modifying factor in the association between high salt intake and TOD. The elevation of 8‐OHdG may be involved in the pathophysiology of TOD induced by salt intake.